The Implementation of Islamic Religious Education Program at the Abab Sub-District Office of Religious Affairs, PALI Regency - Eka Saputra, Darwin; Berlian, Zainal; Zainuri, Ahmad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to analyze the implementation of Islamic religious education services carried out by the Office of Religious Affairs (KUA) of Abab Pali, South Sumatra, in enhancing the community's understanding and practice of Islamic teachings. The research employed a qualitative method with a case study approach. Data were collected through in-depth interviews, direct observations, and document analysis related to the educational programs conducted. The findings reveal that KUA Abab Pali has implemented various programs, including worship training, premarital education, religious education for children and adolescents, and social religious counseling. These programs have successfully improved religious understanding, character development, and societal harmony. However, challenges such as limited human resources, facilities, and varying participant knowledge levels remain. The utilization of technology emerges as a key innovation to enhance program accessibility and effectiveness. In conclusion, the implementation of Islamic religious education in KUA Abab Pali positively impacts the community, though further improvements in resources and strategies are needed to address the challenges. This study is expected to contribute to the development of more effective and sustainable Islamic religious education programs.